Administrative Learning Application Need Analysis for Family Welfare Empowerment (PKK) Education and Training - Rahmawati, Alfi Nur Fitria; Murwaningsih, Tri; Efendi, Agus (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The development of digital technology makes administrative management sk ills have to adapt so that the bureaucracy that organizes Family Welfare Empowerment (PKK) can be maximally implemented. This research is a pre-liminary study that aims to analyze the administrative problems of the PKK through a needs analysis for education and training, including: (1) how ad-ministration is managed; (2) what factors influence administrative manage-ment; and (3) what efforts are needed to resolve administrative problems. The research method used is descriptive qualitative research. The research subjects involved as informants consisted of 10 PKK managers using non-test data collection techniques accompanied by instruments, namely observa-tion sheets and lists of questions. The data analysis technique used is de-scriptive analysis technique. The results of the study found that PKK admin-istrative management was still done manually with administration books, not yet implemented digitally. Factors affecting the administration are internal and external factors. While answering the portrait of PKK administrative management, efforts that can be made are digitizing the PKK administration by making digital applications and training in using the PKK administration application. The results of this study serve as a reference for developing ap- plications as learning media for education and training programs to improve administrative learning practices.